1990
DOI: 10.1037/0021-9010.75.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Personality, affect, and behavior in groups.

Abstract: Building from an attraction-selection-attrition framework (Schneider, 1987) and the socialization literature, this study views personality, affect, and behavior as group-level phenomena. Among a sample of 26 work groups, it was found that individual affect was consistent within groups, suggesting that the affective tone of a group is a meaningful construct. Characteristic levels of the personality traits positive affeclivity and negative affectivity within groups were positively associated with the positive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
1,153
2
30

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,182 publications
(1,219 citation statements)
references
References 53 publications
34
1,153
2
30
Order By: Relevance
“…For instance, Bateman and Organ (1983) reported that the more satisfied employees are, the more practical, helpful, and friendly they are, and Miles, Borman, Spector, and Fox (2002) found that the relation between job satisfaction and organizational citizenship can be sizable. Furthermore, studies reveal that experiencing more positive emotions on the job is associated with both better performance and higher levels of organizational citizenship (e.g., Barrick & Mount, 1993;Deluga & Mason, 2000;George, 1990;George & Brief, 1992). Spector (1997) reviewed evidence showing that satisfied workers have lower turnover and absenteeism than nonsatisfied workers, and are more punctual, cooperative, and helpful to other workers.…”
Section: Conclusion and Cautionsmentioning
confidence: 99%
“…For instance, Bateman and Organ (1983) reported that the more satisfied employees are, the more practical, helpful, and friendly they are, and Miles, Borman, Spector, and Fox (2002) found that the relation between job satisfaction and organizational citizenship can be sizable. Furthermore, studies reveal that experiencing more positive emotions on the job is associated with both better performance and higher levels of organizational citizenship (e.g., Barrick & Mount, 1993;Deluga & Mason, 2000;George, 1990;George & Brief, 1992). Spector (1997) reviewed evidence showing that satisfied workers have lower turnover and absenteeism than nonsatisfied workers, and are more punctual, cooperative, and helpful to other workers.…”
Section: Conclusion and Cautionsmentioning
confidence: 99%
“…Considering the work climate, the benefits of a positive working environment and its impact on organisational performance, employee satisfaction, and employee effectiveness are well documented in the literature and span studies from 1985 by Schneider and Bowen to more recent studies by Kozlowski and Ilgen (2006). Regarding the second trend of good ideas, care, love, and hope, George (1990) found that the overall feelings within an organisation affect how individuals feel about that organisation. Specifically, positive emotions can reduce absenteeism, intention to quit, and conflict while increasing cooperation and job performance (Barsade, 2002;George & Brief, 1992;Jinnett & Alexander, 1999).…”
Section: Healthy Working Conditionsmentioning
confidence: 93%
“…Au travers de la cohésion qu'elle pourrait amplifier, elle favoriserait la performance par une émulation et coopération d'équipe, la spontanéité et la confiance (George, 1989 ;George et Brief, 1992 ;Jones et George, 1998). Les travaux de George (1989 ;1990) démontrent l'influence de l'humeur du groupe sur le comportement prosocial vis-à-vis des collègues, des clients et sur la performance et l'absentéisme. Dernièrement, Barsade (2002) démontre par une expérimentation que l'émotion de groupe influence la dynamique et la performance de groupe.…”
Section: This Paper Presents Research Carried Out At Cirano and Aims unclassified